Gasto público sanitario y contaminantes del aire: un análisis empírico para los países de América Latina periodo 2000 – 2021 - Horna Ushca, Ramiro Xavier (2023)
ABSTRACT: The economy has snowballed in the past few years, resulting in environmental pollution. Latin American countries have a severe concern for public health. A comprehensive analysis of environmental pollutants, economic growth, and public health was carried out using data from 12 Latin American economies from 2000 to 2021. The researcher used minimum modified square panels. The results demonstrated a long-term causality between renewable energies and carbon dioxide (CO2) emissions in healthcare expenditure. Renewable energy and healthcare expenditure are positively and significantly correlated. This study concluded that investment in renewable energy leads to a reduction in air pollution, improvements in healthcare, and the promotion of economic growth.